2005
DOI: 10.1007/s00330-005-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal masses falsely diagnosed as adenomas on unenhanced and delayed contrast-enhanced computed tomography: Pathological correlation

Abstract: Diagnosing adenoma merely on CT numbers can lead to misdiagnosis. The lower specificity than expected is due to pheochromocytomas presenting as false positives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 19 publications
5
36
1
1
Order By: Relevance
“…Although we did not find any clear definition in the literature of "lipidrich" or "lipid-poor" adenomas in terms of pre-contrast CT attenuation, previous researchers have investigated attenuation threshold values of 10 -25 HU when distinguishing adenomas from other masses on pre-contrast CT; in the past decade, a sensitivity of 36% -89% and a specificity of 95% -100% was reported [15][16][17][18][19][20]. Here, we adopted a pre-contrast CT attenuation value of 20 HU to define lipid-poor adrenal adenomas; lesions with less than 20 HU were excluded as these were considered typical lipid-rich adenomas (or some with negative HU, myelolipomas), and lesion with 20 HU or greater attenuation on noncontrast CT that were stable over 6 months or greater were judged to be lipid-poor adenomas.…”
Section: Discussioncontrasting
confidence: 56%
“…Although we did not find any clear definition in the literature of "lipidrich" or "lipid-poor" adenomas in terms of pre-contrast CT attenuation, previous researchers have investigated attenuation threshold values of 10 -25 HU when distinguishing adenomas from other masses on pre-contrast CT; in the past decade, a sensitivity of 36% -89% and a specificity of 95% -100% was reported [15][16][17][18][19][20]. Here, we adopted a pre-contrast CT attenuation value of 20 HU to define lipid-poor adrenal adenomas; lesions with less than 20 HU were excluded as these were considered typical lipid-rich adenomas (or some with negative HU, myelolipomas), and lesion with 20 HU or greater attenuation on noncontrast CT that were stable over 6 months or greater were judged to be lipid-poor adenomas.…”
Section: Discussioncontrasting
confidence: 56%
“…The reason for this is the lack of overlap between the APEW and RPEW values of these two adrenal tumors. However, a few pheochromocytomas were reported to show early strong enhancement and rapid contrast material washout, which mimicked adenomas [5][6][7][8][9]. In particular, Park et al reported that the pheochromocytoma was the most common adenoma-mimicker, which reduced the diagnostic accuracy for adenoma using delayed contrast-enhanced CT [9].…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, there are several reports showing that a few pheochromocytomas had such high washout values on delayed contrastenhanced CT that they mimicked adenomas [5][6][7][8][9]. These studies included a small number of pheochromocytomas and did not adequately evaluate their imaging features of the CT images.…”
Section: Introductionmentioning
confidence: 82%
“…Fourth, non-functioning adenomas were not included because lesions were diagnosed with the imaging study, not with biopsy or surgery. In addition, several non-adenomas with adenoma-like enhancement were not included in the analysis [14,26,27]. These false-positive lesions may decrease CT sensitivity for adenoma.…”
Section: Discussionmentioning
confidence: 94%
“…Adenoma may grow in a varying rate and adenocarcinoma focus may increase during a follow-up period. Pheochromocytoma or adrenal metastasis from renal cell carcinoma may grow as slow as adenoma, when the lesion is small (<3 cm) [14,26,27]. These non-adenomas Fig.…”
Section: Discussionmentioning
confidence: 96%